AL-WUJŪD AL-DZĀTĪ LIL-IMĀM AL-SHĀFI‘Ī FĪ KITĀB DĪWĀN AL-IMĀM AL-SHĀFI‘Ī ‘ALĀ NAẒARIYYAH WUJŪDIYYAH LI- SØREN KIERKEGAARD - Mohammad Rasyid Hidayatullah Roesli; Abdul Basid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to uncover the existential choices of Imam Asy-Syafi’i in his poems in the book